Studi Demografi Perbedaan Stress Akademik Mahasiswa ditinjau dari Keikutsertaan Organisasi, Prestasi akademik, dan Jenis Kelamin - Raihana, Permata Ashfi; Kencana, Shafira Sekar; Dewi, Innayah Kusuma; Ilma, Ashfiya Naila (Universitas Muhammadiyah Metro, 2024)
The COVID-19 pandemic has significantly impacted education, one of which is online learning, an essential change for students that causes academic stress. This research aims to determine differences in academic stress during the pandemic regarding organizational participation, educational achievement, and student gender. The research method used is a quantitative correlational research method. This research was conducted in 2020, and the subjects of this research were 202 psychology students at a university in Surakarta who were selected using an incidental sampling technique. The data analysis technique used is two-way ANOVA. This research results show no difference in academic stress in terms of organizational participation, academic achievement, and gender.